Yeast mutants deficient in protein glycosylation. - Huffaker, T C (1983)
The synthesis of asparagine-linked oligosaccharides involves the formation of a lipid-linked precursor oligosaccharide that has the composition Glc3Man9GlcNAc2. We have used a [3H]mannose suicide selection to obtain mutants in yeast that are blocked in the synthesis of this precursor oligosaccharide. The alg1 mutant accumulated lipid-linked GlcNAc2, alg2 mutants accumulated Man1-2GlcNAc2, alg3 mutants accumulated Man5GlcNAc2, alg4 mutants accumulated Man1-8GlcNAc2, and alg5 and alg6 mutants accumulated Man9GlcNAc2. Some of these mutants appeared to transfer oligosaccharides other than Glc3Man9GlcNAc2 from the lipid carrier to invertase. These aberrant protein-linked oligosaccharides were processed by the addition of outer chain residues in the alg3, alg5, and alg6 mutants. There was virtually no outer chain addition in the alg2 and alg4 mutants. alg4 was the only mutant that failed to secrete invertase.